Primary care physicians’ job satisfaction in eleven Western countries: a cross-sectional study - Enzo Dattoli; Christine Cohidon (BMC Primary Care)
Abstract Purpose Job dissatisfaction and job-related stress among primary care physicians (PCPs) are recognised as major issues in high-income countries. Methods We analysed the Commonwealth Fund’s 2019 International Health Policy Survey of PCPs (n = 13,200). Job dissatisfaction was examined with regard to its potential determinants, including job-related stress, satisfaction with income, time spent with patients, workloads and administrative tasks. We also analysed the future possible consequences of dissatisfaction. We examined outcomes by sex, age and practice location. Results Proportions of PCPs ‘extremely’ or ‘very satisfied’ with their job varied from 33% (France) to 69% (Switzerland). There were strong correlations between PCP job satisfaction and dissatisfaction with salary (OR = 2.64; 95%CI: 2.35–2.96), workload (OR = 2.80; 95%CI: 2.20–3.57) and time spent with patients (OR = 1.91; 95%CI: 1.58–2.31). 47% of physicians did not want to reduce their working hours; 84% did not yet want to retire from work fully (more than 23% after 55 and more than 57% after 65 would like to retire). Conclusions Most PCPs were satisfied with their jobs. Although the variables studied could not explain some of the differences observed, this study’s results could suggest policy avenues for improving PCPs’ job satisfaction (e.g. more inter-professional work; rebalancing different specialists’ salaries).